2021
DOI: 10.1177/17479541211054239
|View full text |Cite
|
Sign up to set email alerts
|

The relative age and birth order effect in Japanese professional football

Abstract: This study examines how the probability of becoming a professional football player depends on the birth month (relative age effect) and birth order. These two factors are random and cannot be controlled by the athlete. If these factors influence the probability of the occurrence of top athletes, they not only create inequality but also close the disciplines to potentially talented athletes, lowering the level of competition. Therefore, in this study, we statistically clarified the presence or absence of “gifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Studies have confirmed this effect across a variety of sports globally, including American football, 2 athletics, 3 basketball, 4 baseball, 5 rugby, 6 football/soccer, 7,8 and ice hockey again. 9 There has also been a number of extensive literature reviews written.…”
Section: Introductionmentioning
confidence: 85%
“…Studies have confirmed this effect across a variety of sports globally, including American football, 2 athletics, 3 basketball, 4 baseball, 5 rugby, 6 football/soccer, 7,8 and ice hockey again. 9 There has also been a number of extensive literature reviews written.…”
Section: Introductionmentioning
confidence: 85%
“…Kawai, et al [17] also investigated U7-U12 grassroots football and found RAE in U9 and U12 categories. Yamamoto, et al [18] explored the probability of becoming a professional player based on birth month and birth order in the J.LEAGUE and found a significant RAE. Further research within elite youth football by Hirose and Hirano [19] examined the relationship between birth month distribution and biological maturation in U9 -U16 players in a J.LEAGUE academy, which explored significant RAE in all age groups, but without evidence of statistically significant differences between biological maturation and birth months.…”
Section: Introductionmentioning
confidence: 99%